Time in the Palace of Dreams - Panariti, Ana (Richtmann Publishing, 2012)
During this work you will come across the concept of time and how it is used in the masterpiece Palace Of Dreams of thefamous and well known albanian writer Ismail Kadare. The concept of time will be treated in different views such as calenderian time,social time, historical time and universal time. Calenderian time would be a connector between the lived time and the cosmic time. Itinvolves in itself documents, archives and datas which are all included in the masterpiece. Meanwhile, the social time is a linking bridgebetween the individual and the society. Mark-Alemi as the main character relies in a X plan within a social time. The insomnia of thecharater breaks the time of sleeping and raises the level of the time of thinking.